Determinants of web-technology and e-business adoption among small and medium travel agencies in Malaysia - Shaharuddin, Nor Asikin (2018)
As the backbone of the economic contributor to Gross National Products (GNP), tourism sector plays a vital role in creating employment opportunities. Travel agencies business is one of the vital sub-segments contributing to the growth of the travel and tour markets. However, there is a concern that small and medium travel agencies (SMTAs) have yet adopted and use effectively, or even have used, web-technology and e-business application. Therefore, there is a gap that lies between the ideal and the reality of the actual usage of web-technology and e-business as sources of competitive advantage among (SMTAs) in Malaysia. This study aims to provide an explanation on how business potentials can increase capabilities via the use of effective e-business strategies to capture greater % of the market. This study investigates (a) a direct relationship between the Innovational, Organizational and Environmental characteristics (IOE) and competitive advantage (CA) of SMTAs, (b) the role of webtechnology and e-business adoption (WEA) as a mediator in the relationship between IOE and CA and (c) decision makers’ characteristics (DMC’s) that moderate the relationship between WEA and CA. Nine hypotheses were proposed in relation to the determinants of WEA and CA. The data was then analyzed using fifteen variables of IOE context towards five WEA context, four decision makers’ characteristics context, and six competitive advantage contexts. In comparison to previous studies, this study proposes e-resources of SMTAs, data secrecy and confidentiality and training & human capital investment as the new variables for the predicting factors influencing WEA. Additionally, 4 DMC’s of owners-managers age, educational level, years of experience, and ICT knowledge has been introduced in this study. In order to SMTAs to wider its business globally and remain its position in the industry, this study introduced six CA variables that were all significantly related to IOE characteristics and WEA. A total of three hundred twenty-three (323) respondents were selected through a simple random sampling technique from five regions of Malaysia. Data was gathered using structured questionnaire adopted from the previous literature and the questionnaire was administered by the researcher. The analysis was completed using statistical program for social science (SPSS) and structural equation modeling (SEM), AMOS software. The findings revealed that, the Innovational (ICs) and Organizational characteristics (OCs) have significantly contributed to WEA activities among SMTAs in Malaysia, while in contrast Environmental characteristics (ECs) do not contribute to WEA. Additionally, all IOE characteristics were reported as significantly related to CA. Furthermore, this study was carried out to study the role of moderators that affects the decision of owner-managers (age, level of education, experience and ICT knowledge) between IOE characteristics and web-technology and ebusiness adoption. Age category was found to have a significant relationship between ICs and OCs and WEA. This study also revealed that the education level is the only DMCs that moderated the relationship between ICs and WEA as the other DMCs moderators were found as not significantly contribute for WEA. Additionally, WEA were found as mediated the relationship between the ICs and CA and OCs and CA. SMEs entrepreneurs must equip young managers with innovative skills and knowledge to further develop their business at a global level. Owner-managers with the higher qualification of master’s degree and above have the capabilities to steer the business direction at a greater success. As a continuation of the previous studies on the role of ICT to the development of the business of SMTAs, this research studied the relationship between IOE determinants and WEA and CA. The aspect of CA is measured in product development, quality of services, price competitiveness, accessibility and connectivity, firm branding and human resources development. This result indicated that the owner-managers of SMTAs business must exploit the web-technology and e-business function to improve their business at the innovational and organizational level to further develop its competitive advantage among SMEs business. The findings could be utilized by a variety of stakeholders such as the Ministry of Tourism and Culture Malaysia (MOTAC), Malaysia Association of Tour and Travel Agents (MATTA), Bumiputra Association of Tour and Travel Agents of Malaysia (BUMITRA) and SMTAs in designing a systematic policies & procedure related to ICT infrastructure and online facilities to further develop Malaysia tourism industry.